Crotalaria shrirangiana (Fabaceae): A new rattlepod from the Western Ghats of India - Rokade, Krishnat; Dalavi, Jagdish Vishnu; Gaikwad, Swaroopsingh; Gaikwad, Nikhil (Phytotaxa, 2020)
Crotalaria shrirangiana is described and illustrated as a new species in the present communication. The new species is found growing in northern Western Ghats ranges of Maharashtra. It is an erect, profusely branched under-shrub up to 1.5 m in height, with bright yellow flowers. It shows close affinities with Crotalaria juncea but is distinguished by details of its stem indumentum, shape and size of the leaves, inflorescence, bracts and bracteoles, shape and size of the flowers, standard petal, pod size and number of seeds per pod.